2020
DOI: 10.1186/s43163-020-00025-1
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of ultrasonography in detection of different types of thyroid nodules

Abstract: Background This article discusses the importance of high frequency ultrasonography in detection of different types of thyroid nodules considering only the histopathological examination of the surgical specimens as the final diagnosis. We studied 50 patients referred to ENT clinic with a thyroid nodule. Ultrasonography and ultrasound-guided fine-needle aspiration biopsy were done to all the patients. Thyroid surgery was done according to FNAB results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…However, the latter statement is generally acceptable if only the diagnostic procedures implemented the US guidance especially for some complex nodules or posteriorly located nodule; unquestionably increasing its Acc either anatomically or histopathological investigation in advance [12], [15], [16]. Our findings of FNAB (without US-guided) accuracies parameter were similarly reported in a recent study by Youssef et al, in 2020, in which stating the Sn, Sp, PPV, and NPV value of US-guided FNAB for 37.5%, 100.0%, 100.0%, and 77.27%, respectively; for a review purpose, the same study applied the utilization of Bethesda scoring method for its nodule status determination (I-IV for benign and V-VI for malignant) with p-value of 0.001 in the its diagnostic performance analysis [17]. Another study by Bozbiyik et al, in 2011, demonstrate similar value of accuracies parameter value to determine the diagnosis in large thyroid nodules as compared to Youssef et al and our study.…”
Section: Discussionsupporting
confidence: 84%
“…However, the latter statement is generally acceptable if only the diagnostic procedures implemented the US guidance especially for some complex nodules or posteriorly located nodule; unquestionably increasing its Acc either anatomically or histopathological investigation in advance [12], [15], [16]. Our findings of FNAB (without US-guided) accuracies parameter were similarly reported in a recent study by Youssef et al, in 2020, in which stating the Sn, Sp, PPV, and NPV value of US-guided FNAB for 37.5%, 100.0%, 100.0%, and 77.27%, respectively; for a review purpose, the same study applied the utilization of Bethesda scoring method for its nodule status determination (I-IV for benign and V-VI for malignant) with p-value of 0.001 in the its diagnostic performance analysis [17]. Another study by Bozbiyik et al, in 2011, demonstrate similar value of accuracies parameter value to determine the diagnosis in large thyroid nodules as compared to Youssef et al and our study.…”
Section: Discussionsupporting
confidence: 84%
“…Even though FNAB is the method of choice, the first step taken in evaluating any thyroid nodule is the use of ultrasonography. This is followed by FNAB, which decides whether the patient will undergo surgical management or not [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study results have concluded that the sensitivity of the ultrasonography in the confirmation of a malignant thyroid lesion in 59.4% and its specificity was 74.3%. In comparison, Youssef et al have concluded in a similar study that the sensitivity of ultrasonography in detecting was 100% with a specificity of 94.12% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modified GLCM: Consider an image g(y, z) of size M × N with L gray levels. Moreover, the GLCM of the image that carries the information regarding the intensities transition among the nearby pixels is determined as in Equation (5).…”
Section: Feature Extractionmentioning
confidence: 99%
“…The amount of thyroid hormones is connected with hypothyroidism and hyperthyroidism. Moreover, the excess thyroid hormone leads to hyperthyroidism associated with low cholesterol level, gluconeogenesis, and weight loss 3‐6 . The reduced thyroid hormone level may lead to hypothyroidism which is characterized by reduced gluconeogenesis, high cholesterol level, and weight gain 7,8 .…”
Section: Introductionmentioning
confidence: 99%